Bupropion for amphetamine withdrawal syndrome - Chan-Ob T. (2014)
This study was a case report of an amphetamine abuser who came to see doctor because of amphetamine withdrawal syndrome three days after stopping prolonged use of amphetamine. The patient was treated him with a slow-release bupropion at the dose of 150 mg per day. After taking bupropion, his withdrawal symptoms i.e. dysphoric mood, fatigue, somnolence, and psychomotor retardation gradually disappeared within two to three days. Moreover, his craving for amphetamines was absent. The authors discussed the possible application for the clinical use for amphetamine abusers or dependence.